ENVIRONMENTAL QUALITY ASSESSMENT OF THE UBERABINHA RIVER-MG USING A RAPID ASSESSMENT PROTOCOL, BIOINDICATORS AND PHYSICOCHEMICAL WATER QUALITY PARAMETERS: - Vasconcelos, Maria da Graça; Paim, Cecília Veras; Capanema, Georgia de Almeida; Silva, Maria Eliete; Carbone, Samara (Editora Impacto Científico, 2025)
Urbanization processes have been causing various impacts on aquatic ecosystems. The purpose of this research was to assess the environmental quality of the Uberabinha River in the municipality of Uberlândia, Minas Gerais, at three sampling points. The purpose of this research was to assess the environmental quality of the Uberabinha River upstream and downstream of the municipality of Uberlândia, Minas Gerais. The research consisted of applying a rapid assessment protocol for habitat diversity, studying benthic macroinvertebrates using the adapted Biological Monitoring Working Party (BMWP) Index, and assessing the physical and chemical parameters of the water. The water samples collected were evaluated for temperature, pH, color, turbidity, conductivity, and dissolved oxygen. The values of the parameters obtained at the three points and in the two collections remained in accordance with CONAMA Resolution 357/2005, with the exception of color, which was higher than the established value in all samples. Only the point upstream of the municipality presented benthic macroinvertebrates sensitive to pollution. With the results of the rapid assessment protocol applied to the analyzed sections of the river, it was possible to verify that both fell into the altered section category. The results obtained show that the water quality of the river changes from upstream to downstream of the city, leading to the conclusion that the Uberabinha River is suffering significant anthropogenic interference, both in the rural area upstream and in the urban area downstream of the municipality, presenting a situation that requires greater control and investigation to restore the environmental quality of this ecosystem.DOI: https://doi.org/10.56238/edimpacto2025.089-001